Political leadership in Turkey and Recep Tayyip Erdogan - Temiz, Suleyman; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
It examines political change in Turkey under the leadership of Recep Tayyip Erdogan during his premiership from 2002 to 2014 in order to present the portrait of Erdogan as a political leader. The interactive approach was employed to structure this analysis. In line with this approach, external and internal resources on Erdogan’s leadership are utilised. External resources are considered with regard to institutional and non-institutional aspects. The non-institutional resources referred to the main characteristic of socio- economic condition of the state and relationship with the political regime and its secular representatives.